RETRACTED: Management of Sustainable Development of Car Service Enterprises - Dembitskyi Valerii; Murovanyi Igor; Maiak Mykola; Pavlova Iryna; Popovych Pavlo; Borysiak Olena; Brych Vasyl; Karolina Mucha-Kuś (E3S Web of Conferences, 2023)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002